Exploring the Roles of In-Network Caching in ICN - Xiaoyan Hu; Jian Gong (Dianxin kexue)
The universal in-network caching, as a prominent feature of information centric networking（ICN）, plays important roles in the demonstration of ICN's advantages over other architectures. But so far, many people still have different perception of it. The specific roles that in-network caching can play should be first explored before it can be taken full advantage were argued. Such exploration by pointing out three levels of in-network caching were argued, explained how the three-level in-network caching play roles in error-recovery, flash crowd relief, DDoS attack prevention, popular content hosting and commission service, and stating issues related to these roles.